Accelerating the speed of innovative anti-tumor drugs to first-in-human trials incorporating key de-risk strategies - Yuqi Wang; Quan Quan; Camille Gleason; Helin Yu; Lujia Peng; Yanshen Kang; Ling Jiang; Kailun Wu; Jie Pan; Moxiyele Bao; Qing Zhu; Meiqi Yi; et al. (mAbs)
Pharmaceutical companies have recently focused on accelerating the timeline for initiating first-in-human (FIH) trials to allow quick assessment of biologic drugs. For example, a stable cell pool can be used to produce materials for the toxicology (Tox) study, reducing time to the clinic by 4–5 months. During the coronavirus disease 2019 (COVID-19) pandemic, the anti-COVID drugs timeline from DNA transfection to the clinical stage was decreased to 6 months using a stable pool to generate a clinical drug substrate (DS) with limited stability, virus clearance, and Tox study package. However, a lean chemistry, manufacturing, and controls (CMC) package raises safety and comparability risks and may leave extra work in the late-stage development and commercialization phase. In addition, whether these accelerated COVID-19 drug development strategies can be applied to non-COVID projects and established as a standard practice in biologics development is uncertain. Here, we present a case study of a novel anti-tumor drug in which application of “fast-to-FIH” approaches in combination with BeiGene’s de-risk strategy achieved successful delivery of a complete CMC package within 10 months. A comprehensive comparability study demonstrated that the DS generated from a stable pool and a single-cell-derived master cell bank were highly comparable with regards to process performance, product quality, and potency. This accomplishment can be a blueprint for non-COVID drug programs that approach the pace of drug development during the pandemic, with no adverse impact on the safety, quality, and late-stage development of biologics.